Examine the Role of Subsidies on Water Use Efficiency in Parts of Iran - Alireza Shakibaee (Ph.D) (مجله توسعه و سرمایه, 2018)
The importance of water and water economy grows every day. Many economists believe the economic good water scarce in the world. The more important issue is Iran, because Iran is a water scarce country and the world average is 3.1 average precipitation in Iran, so Iran to issue water economy should be given double. Subsidies and reform of water prices, water management is one of the tools. This method since 1388 under the subsidy is running in Iran. The purpose of this paper is to compare the performance of the provinces with each other in water consumption is in the period before and after subsidies. For this study, BCC output oriented, data envelopment analysis DEA is a nonparametric methods have been used. The efficiency of the separation of rural and urban regions in the country in two years, 85 and 90 is estimated to be discussed and compared them to 85 years as the year before subsidies and subsidies year after 90 years as intended Are. The results show that household consumption is character villages, but this is not true in cities, villages and lack of sensitivity indicator is sensitive to price changes cities.